The ugly duchess : beauty & satire in the Renaissance - Capron, Emma (National Gallery Global, 2023)
Quinten Massys' An Old Woman ('The Ugly Duchess') is one of the Renaissance's most famous faces. In a fresh review of the iconic image, this book unveils the painting's original context: its status as a pioneering work of satirical art, its debt to Leonardo da Vinci's grotesque drawings, and what it tells us about the period's complex attitudes towards women, age and normative beauty. The painting and its partner, An Old Man, are parodic portraits that mock the supposed lust and vanity of older women. Yet a closer look also reveals a figure defiantly flouting conventions and a painter subverting artistic expectations. The publication traces the eventful afterlife and enduring power of this seminal image: how she gained her nickname 'The Ugly Duchess' and inspired John Tenniel's much-loved illustrations of Lewis Carroll's Alice's Adventures in Wonderland (1865), capturing the imagination of generations of readers. Exhibition: National Gallery, London, UK (16.03.2023-11.06.2023)